If it's not appropriate for women - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The 1999 Zimbabwe International Book Fair held in Harare last August. Under the theme of Women s voices: gender, books and development, an intensive programme of workshops, seminars and encounters focussed on the gender aspects of publishing in Africa